Self‐incompatibility limits sexual reproduction rather than environmental conditions in an invasive water primrose. Issue 2 (29th March 2021) - Portillo Lemus, Luis O.; Bozec, Michel; Harang, Marilyne; Coudreuse, Julie; Haury, Jacques; Stoeckel, Solenn; Barloy, Dominique
Abstract: Fruit‐set and seed‐set depend on environmental conditions and reproductive systems. They are important components of sexual reproductive success in plants. They also control the ecological success and adaptation of invasive plants within their non‐native ecosystems. We studied which factors bring about fruit‐set and seed‐set in invasive populations of the aquatic plant Ludwigia grandiflora subsp. hexapetala . We analyzed fruit set and seed set in 37 populations growing under variable climatic conditions in Western Europe. Sub‐samples of seven fruitful and fruitless populations were grown in common controlled conditions. We carried out self‐ and cross‐pollinations, and measured the floral morphometry. Environmental conditions did not affect fruit‐set and seed‐set in‐situ and in common controlled environments. Hand‐pollinations showed that individuals from fruitful populations exhibited fruit and seed production whatever the pollen donor, whereas individuals from fruitless populations only did so when pollen came from fruitful populations. Floral morphometry evidenced the existence of two floral morphs that fully overlapped with fruitfulness, and individual incompatibility. Our results rebutted the hypothesis that environmental variations control fruit set and seed set in these invasive populations. We instead showed that fruit set and seed set were controlled by a heteromorphic reproductive system involving a self‐incompatible and inter‐morph compatible morph (long‐styled morph), and a self‐ and inter‐morph compatible reverse morph (short‐styled morph). We collected morphs and fruit set records of this species worldwide and found the same relationship: fruitless populations were all composed only of individuals with long‐styled floral morph. Our study constitutes the first evidence of a heteromorphic self‐incompatible system in Ludwigia genus and Onagraceae family.